Desarrollo de un software para la gestión de los procesos de autoevaluación con fines de acreditación de las Universidades y Escuelas Politécnicas del Ecuador. - Cornejo Chalán, David Alonso (2010)
The beginning of the software development was given at the beginning of August in 2007 with the totally study of all the details that the autoevaluation process has, and the CONEA manager of it guide. Once obtained the enough knowledge you proceeded to make a meticulous study of programming tools that it would help us to the development of the present software, and as a result of this study we solved to use tools such as: in relation to database Mysql, programming language C# and as a programming tool Visual Microsoft Studio 2005. The present software to make agile the development Autoevaluation process of Universities and Polytechnic Schools, and it realize subprocesos like: registration, elimination and modification of each one of the relating of quality (function, environment, characteristic, standard, indicator, data and informants of quality). These relating of quality are the essential part of the whole process of Autoevaluation because the CONEA determines them, for that reason that the registration of informants of quality like the existence of each one of these relating will make possible the normal operation of the software. Also these they will help as to the generation of each one of the techniques and instruments of the Autoevaluation, which will allow us the summary of all the information that each one of the relating quality that is required once according to all aspects that it characterizes them once, generated these techniques, the software allows the immediate entrance of all the information and results that we has been able to gather of each one of the relating informants associated to its respective ones of quality. The information obtained by the system is treated chard foreseen to the moment to generate each one of the techniques and instruments, in the case of the technique Interviews - Guides and Survey - Questionnaire the questions associated to a certain indicator can be you consider of Opinion or Closed, in the case of being a question of Opinion, it is considered the average of the total value of ponderation of this question, in the case of being a Closed question, it is considered the total (I roof) of the value of ponderation of this question; when it is technique Guide of Observation the value that will take of each one of the questions related to this it will be the average and the lastly the technical Documental Analysis that not structured by a series of questions but it is guided to check the existence of documents that certain indicator and informant requires, the obtained information will be value ted with the total (roof) of the value ponderation of the indicator. This appreciation of valuation of each one of the applied techniques will allow us the obtaining of the cuali-quantitative results of each one of the relating quality that in this case: will be function, ambits, characteristic, standard and indicators. The information will be analyzed based on: function - ambit - characteristic, steps that are required to be able to analyze the information, once certain the characteristic the software realize an internal process, to throw the results of standard and indicative, this process is summarized in the following thing: 1. To look for the number of indicators that the characteristic has, 2. With each one of these indicators (one to one), their existence will be verified inside of a technique, first relating it directly to an informant and then to each one of the techniques that to this has been assigned (This process will repeat with all the existent informants and with all the indicators (179) existent), 3. After was have proven their existence inside an informant and a technique you proceeds to analyze the results entered in quantitative form, this information will be obtained based on the total number of informants that it technique entered. 4. Once obtained the results of each one of the indicators related to a characteristic, these indicators are related one to one to their respective one standard, for this way to be able to obtain the pondered value of each one of the standards, for this I calculate only we make reference to the number of indicators that the standard has and add the obtained pondered value of each one the indicators. 5. To obtain the pondered value of the characteristics the total number of standards it is obtained that are related to a characteristic, and the same as it was made for the standards and obtained the pondered value of the standards and the pondered value of the characteristic. 6. This process repeats as a ambit as a functions. Once obtained all the information of all the relating of quality, this information will be presented in a series of reports that the CONEA requests each one of the Superior Education institution.